2013
DOI: 10.1098/rspb.2012.2302
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of wing pattern alleles and speciation via homoploid hybridization inHeliconiusbutterflies: a review of evidence from the genome

Abstract: The diverse Mü llerian mimetic wing patterns of neotropical Heliconius (Nymphalidae) have been proposed to be not only aposematic signals to potential predators, but also intra-and interspecific recognition signals that allow the butterflies to maintain their specific identities, and which perhaps drive the process of speciation, as well. Adaptive features under differential selection that also serve as cues for assortative mating have been referred to as 'magic traits', which can drive ecological speciation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 98 publications
0
28
0
Order By: Relevance
“…In other words, there appears to be strong evidence of adaptive introgression of protective warning wing colour variation between closely related Heliconius species. Brower () suggested that mimetic patterns in Heliconius have evolved without apparent hybridization although his claims appear inconsistent with the bulk of research indicating introgression (for a detailed discussion, see Eratosignis ,b).…”
Section: Examples Of Adaptive Introgressionmentioning
confidence: 99%
“…In other words, there appears to be strong evidence of adaptive introgression of protective warning wing colour variation between closely related Heliconius species. Brower () suggested that mimetic patterns in Heliconius have evolved without apparent hybridization although his claims appear inconsistent with the bulk of research indicating introgression (for a detailed discussion, see Eratosignis ,b).…”
Section: Examples Of Adaptive Introgressionmentioning
confidence: 99%
“…Such variation within a population is sometimes stably maintained as alternative ecological strategies (Cabral et al 2008). For example, in the mimetic butterfly Heliconius numata (Cramer, 1780), several discrete wing color patterns are maintained in sympatry, which are under the genetic control of a single supergene locus (Joron et al 2006(Joron et al , 2011Brower 2013). In the adzuki bean beetle Callosobruchus chinensis (Linnaeus, 1758) and the red flour beetle Tribolium castaneum (Herbst, 1797), duration of death-feigning behavior was variable within a population.…”
Section: Introductionmentioning
confidence: 99%
“…In both mammals [88] and arthropods [89, 90], a single instance of hybrid speciation has been well described. Interspecies hybridization typically results in complicated relationships within species complexes, characterized by indistinct species borders.…”
Section: Introductionmentioning
confidence: 99%